Looptempo voorspelt verschillen in niveau van cognitief functioneren - Diesfeldt, Han F.A. (Tijdschrift voor Gerontologie en Geriatrie, 2014)
Bespreking:Mielke, M.M., Roberts, R.O., Savica, R., Cha, R.,Drubach, D.I., Christianson, T., Pankratz, V.S., Geda,Y.E., Machulda, M.M., Ivnik, R.J., Knopman, D.S.,Boeve, B.F., Rocca, W.A. & Petersen, R.C. (2013).Assessing the temporal relationship between cognitionand gait: slow gait predicts cognitive decline in theMayo Clinic Study of Aging. Journal of Gerontology:MEDICAL SCIENCES, 68, 929–937.